Analisis Komponen Biaya Produksi Pembangunan Rumah Tinggal 2 Lantai Berdasarkan Work Breakdown Structure (WBS) - vina vina amaliyah; Amri Gunasti (Journal of Science and Engineering, 2026)
This study aims to develop a Work Breakdown Structure (WBS) for a two-story residential construction project, analyze production cost components based on each work group, and determine the cost distribution within the project. The research method used is a quantitative descriptive method utilizing secondary data in the form of working drawings, technical specifications, work volumes, and unit prices. The research stages include WBS preparation, work volume calculations, work unit price analysis (AHSP), preparation of a Cost Budget Plan (RAB), and cost distribution analysis based on the WBS structure. In a study on the Analysis of Production Cost Components for the Construction of a Two-Story Residential House based on a Work Breakdown Structure (WBS), the use of a WBS simplifies and streamlines the work identification process compared to using this approachCost analysis based on the WBS indicates that each work group has a different cost contribution to the total project cost. Structural work, including foundations, footings, columns, beams, floor slabs, and stairs, is the work component that contributes the most to costs due to the high material and labor requirements. Furthermore, the implementation of a WBS has been proven to improve the accuracy of RAB preparation, facilitate cost control, and assist in project monitoring and evaluation during construction.